Adopting a multidisciplinary approach to maximising performance during military visual search tasks. Issue 2 (9th April 2019) - Cornes, Katherine R; Boardman, M; Ford, C; Smith, S
Abstract : During the conflicts in Afghanistan and Iraq, many UK military personnel were killed or injured by improvised explosive devices (IEDs). Insurgents sought to develop new ways of concealing and detonating IEDs, and UK forces invested significantly in finding increasingly effective methods of detecting and avoiding them. Between 2010 and 2014 the UK's Defence Science and Technology Laboratory's Human and Social Sciences Group (HSSG) was asked to investigate the factors that might affect the performance of specialist search teams in the identification of IEDs. They sought to ascertain ways to improve effectiveness and maximise safety through training, human factors advice on equipment design, and recommendations on changes to tactics techniques and procedures. This paper provides a short summary of some of the research conducted that underpinned the advice and recommendations that were provided. The research conducted by HSSG, in collaboration with industry and academia, helped ensure that search teams had the best possible training, advice and equipment.